Mechanical and electrical properties of self-healable rubber blends under influence of imidazole mixture and selective wetting of hybrid filler - Le Hong Hai; Hoang Xuan Tung; Yashwanth Sai Anjaneya Varma Kosuri; Subhradeep Mandal; Kedar Nath Dhakal; Rameshwar Adhikari; Beate Langer; Sven Wiessner (eXPRESS Polymer Letters, 2024)
Flexible rubber composites based on blends of bromobutyl rubber (BIIR)/epoxidized natural rubber (ENR) filled with a hybrid filler of layered double hydroxides (LDH)/carbon nanotubes (CNT) were prepared, which may be of interest for use in tires and inner liner. An imidazole mixture of butyl-imidazole and 1H-imidazole was proposed to achieve reversible non-covalent networks consisting of ionic clusters and hydrogen bonding that led to the self-healing properties of each blend phase. The objective of the present work was to characterize the effects of selective modification of the rubber blends by imidazole and selective wetting of the hybrid filler on the mechanical and electrical properties and the self-healing effectivity. The wetting concept used to characterize the selective wetting of a single filler in a rubber blend was further developed for a hybrid filler in BIIR/ENR blends. During the one-step mixing and the masterbatch mixing process, re-localization of the hybrid filler between the blend phases under thermodynamic driving forces was observed. Within the specified mixing time, the thermodynamic equilibrium state of filler localization could not be reached. The nearly uniform distribution of LDH in both blend phases and the preferential localization of CNTs in the ENR matrix were found to be essential in giving the BIIR/ENR blends the best combination of self-healing properties and electrical conductivity. The high electrical conductivity of the composites can be exploited to generate a high temperature locally at the damage site inside the rubber samples when an electrical voltage is applied, resulting in an acceleration of the self-healing process.